The Market Interpretation of Management Earnings Forecasts as a Predictor of Subsequent Financial Analyst Forecast Revision - Baginski, Stephen P.; Hassell, John M. (The Accounting Review, 1990)
[This study investigates the relation between financial analyst earnings forecast revisions and two independent variables: (1) a measure of management earnings forecast news issued prior to analyst revisions, and (2) measures derived from the security market price reaction to that news. Results indicate that security price reactions to management forecasts are useful in predicting subsequent analyst forecast revisions. Furthermore, the explanatory power of price reaction is a function of the timing of the management forecast release.]